RANCANG BANGUN SISTEM INFORMASI PENGOLAHAN DATA HASIL TANGKAPAN PERAIRAN UMUM DARAT - Iin Seprina; Evi Yulianingsih (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
Local wisdom is used to create order and balance between social life, culture, and the preservation of natural resources. Some areas in Indonesia include general types of water bodies including: artificial lakes, ponds, Rama, creeks, Keramasan River, Musi River, Keramasan River, and rivers. Production results in the type of Regional Public Waters contribute to the growth of employment and the very high demand for public protein. For this reason, a system is needed that can bridge officers and fishermen with the fish that have been caught starting from the specifications of what types of fish are caught and the total catch is recapitulated in a quarterly period. The System Development Method used in making this Information System uses Rapid Application Development (RAD). which has the following stages: Requirement Planning, Workshop Design, Implementation. The result is a system that can accommodate fishermen's data, catches and annual reports based on the type of Inland Public Waters (PUD).